Pittsburgh International Airport : battling turbulence in the airline industry - Land, Hunter M.; Elston, Lauren P.; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Opened in 1992, the Pittsburgh International Airport midfield terminal complex was designed and built for the hub operations of USAir. Fifteen years and two bankruptcies later, US Airways has reduced what was its largest hub to a focus city with only 68 daily flights. As the airport sits half abandoned, the Allegheny Country Airport Authority is working against an industry in turmoil to rebuild service at the airport.
Originally published: Land, H. M., Elston, L. P., & ORourke, J. S. (2008). Pittsburgh International Airport: Battling turbulence in the airline industry. 08-10. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Pittsburgh International Airport (Pa.); US Airways; Airlines -- Pennsylvania -- Pittsburgh